Rue et marginalité : le cas de Londres au XIXe siècle - Didier Revest (Revue Française de Civilisation Britannique)
Both the capital’s better-off classes and the press, who were always quick to denounce what they saw as the unacceptable ways of the poor, tended, mistakenly, to see the streets of nineteenth-century London as places essentially characterised by prostitution, begging and thieving. Indeed, this misinterpretation resulted in an attack on the poor, aimed at raising raise them up morally, as their difficulties, it was thought, could only stem from improvidence, intemperance, and, more generally, from a disposition to dishonesty. But fighting poverty as such – poverty which was the main reason why thousands of people could exist nowhere but on the fringe – never really featured high on the social and political agenda of the day.